African agriculture within the world economic environment - Tubiana, Laurence (Technical Centre for Agricultural and Rural Cooperation, 1994)
The decade 1980-1990 has in many respects been unfavourable for African countries. The economic recession in the OECD, financial restrictions, the collapse in the price of raw materials and the increase in the number of more dynamic competitors on...